Analysis of The Professionalism of Prospective Physical Education Teachers Viewed from Eight Teaching Skills - Yahya Eko Nopiyanto; Sugihartono, Tono; Andes Permadi; Ipa Sari Kardi; Cahyo Wibowo; Syafrial (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This research aims to determine the professionalism of prospective physical education teachers viewed from eight teaching skills. This research is a quantitative descriptive study with the primary focus of the study being to analyze the professionalism of prospective physical education teachers in terms of eight teaching skills. The population in this study was 83 prospective physical education teachers who attended micro teaching lectures in the even semester of the 2024/2025 academic year. A purposive sampling technique was used for this study. The selected sample had met the established criteria, namely: attending lectures more than 80% or at least 13 meetings, and being willing to be a research sample. Based on these criteria, there were 53 prospective physical education teachers. The data collection technique used a questionnaire consisting of thirty statements. Data was analyzed using percentages with five categories. The results of this study indicate that the teaching skills of prospective physical education teachers are at a good to excellent level, particularly in the areas of providing reinforcement, asking questions, and managing the classroom. However, the aspect of guiding small group discussions still requires special attention in coaching to ensure more equitable learning quality across all teaching skill indicators. It can be concluded that prospective physical education teachers are professional, as seen from the eight teaching skills.